Communicating and sharing working relationships with older employees - Wok, Saodah (Emerald Group Publishing Limited, 2013)
Purpose – This paper seeks to examine the perception of young employees on working relationships satisfaction with communicative teamwork, mutual learning, participative decision making, and communicating feedback of the older employees in higher learning institutions in Malaysia. Design/methodology/approach – A specially-constructed questionnaire was developed for data collection. A total of 575 employees in five Malaysian universities in the Klang Valley participated in the study. Finding – Young employees have positive teamwork relationships with the older employees. They learned a lot from the older employees as the older employees are helpful in sharing their experiences in decision making. At the same time, the young employees receive positive feedback from the older employees. However, the older employees hardly compliment the young employees for their achievements. Research limitations/implications – The current findings provide implications for future organisational and intergenerational research since most communication investigations are Western-biased. Practical implications – The findings can help both the older and the young employees have a better understanding of communication at workplace. Each generation is shaped by its experiences, which brings a variety of strengths to the workforce. Originality/value – This study is unique because it examines an important issue which very little study has been conducted on the issue; the intergenerational communication in organisational setting in Asian perspectives. Keywords Intergenerational communication, Communicative teamwork, Mutual learning, Participative decision making, Older workers, Young employees, Interpersonal communication, Malaysia Paper type Research paper